Tear miRNAs Identified in a Murine Model of Sjögren’s Syndrome as Potential Diagnostic Biomarkers and Indicators of Disease Mechanism - Kakan, Shruti Singh; Edman, Maria C.; Yao, Alexander; Okamoto, Curtis T.; Nguyen, Annie; Hjelm, Brooke E.; Hamm-Alvarez, Sarah F. (Frontiers in Immunology, 2022)
Objective: The tear miRNAome of the male NOD mouse, a model of ocular symptoms of Sjögren’s syndrome (SS), was analyzed to identify unique miRNAs. Methods: Male NOD mice, aged 12-14 weeks, were used to identify tear miRNAs associated with development of autoimmune dacryoadenitis. Age- and sex-matched male BALB/c mice served as healthy controls while age-matched female NOD mice that do not develop the autoimmune dacryoadenitis characteristic of SS were used as additional controls. Total RNA was isolated from stimulated tears pooled from 5 mice per sample and tear miRNAs were sequenced and analyzed. Putative miRNA hits were validated in additional mouse cohorts as well as in tears of SS patients versus patients with another form of dry eye disease, meibomian gland disease (MGD) using qRT-PCR. The pathways influenced by the validated hits were identified using Ingenuity Pathway Analysis. Results: In comparison to tears from both healthy (male BALB/c) and additional control (female NOD) mice, initial analysis identified 7 upregulated and 7 downregulated miRNAs in male NOD mouse tears. Of these, 8 were validated by RT-qPCR in tears from additional mouse cohorts. miRNAs previously implicated in SS pathology included mmu-miR-146a/b-5p, which were significantly downregulated, as well as mmu-miR-150-5p and mmu-miR-181a-5p, which were upregulated in male NOD mouse tears. All other validated hits including the upregulated miR-181b-5p and mmu-miR-203-3p, as well as the downregulated mmu-miR-322-5p and mmu-miR-503-5p, represent novel putative indicators of autoimmune dacryoadenitis in SS. When compared to tears from patients with MGD, miRNAs hsa-miR-203a-3p, hsa-miR-181a-5p and hsa-miR-181b-5p were also significantly increased in tears of SS patients. Conclusions: A panel of differentially expressed miRNAs were identified in tears of male NOD mice, with some preliminary validation in SS patients, including some never previously linked to SS. These may have potential utility as indicators of ocular symptoms of SS; evaluation of the pathways influenced by these dysregulated miRNAs may also provide further insights into SS pathogenesis.